The Effect of Keyboard-Based Word Processing on Students With Different Working Memory Capacity During the Process of Academic Writing. (July 2017) - Van Der Steen, Steffie; Samuelson, Dianne; Thomson, Jennifer M.
This study addresses the current debate about the beneficial effects of text processing software on students with different working memory (WM) during the process of academic writing, especially with regard to the ability to display higher-level conceptual thinking. A total of 54 graduate students (15 male, 39 female) wrote one essay by hand and one by keyboard. Our results show a beneficial effect of text processing software, in terms of both the qualitative and quantitative writing output. A hierarchical cluster analysis was used to detect distinct performance groups in the sample. These performance groups mapped onto three differing working memory profiles. The groups with higher mean WM scores manifested superior writing complexity using a keyboard, in contrast to the cluster with the lowest mean WM. The results also point out that more revision during the writing process itself does not inevitably reduce the quality of the final output.